The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1074/jbc.m113.541672
|View full text |Cite
|
Sign up to set email alerts
|

YfgM Is an Ancillary Subunit of the SecYEG Translocon in Escherichia coli

Abstract: Background:The Sec translocon mediates protein secretion in all organisms. Results: YfgM interacts with the Sec translocon and is part of a periplasmic chaperone network in Escherichia coli. Conclusion: We propose that YfgM mediates protein transfer from the Sec translocon to periplasmic chaperones. Significance: This study provides a better understanding of the composition of the Sec translocon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 59 publications
(75 reference statements)
7
51
0
1
Order By: Relevance
“…Although these putative substrates did not contain any obvious sequence similarities, it is anticipated that their trafficking into the envelope takes place through the SecYEG translocon, as we did not detect any known substrates of the Twin Arginine Translocation (TAT) system (33), or YidC (when independent of SecYEG) (34). This observation is consistent with the observation that YfgM operates at the SecYEG translocon (13).…”
Section: Comparative Proteomic Analyses Of Strains Lacking Yfgm-supporting
confidence: 79%
See 3 more Smart Citations
“…Although these putative substrates did not contain any obvious sequence similarities, it is anticipated that their trafficking into the envelope takes place through the SecYEG translocon, as we did not detect any known substrates of the Twin Arginine Translocation (TAT) system (33), or YidC (when independent of SecYEG) (34). This observation is consistent with the observation that YfgM operates at the SecYEG translocon (13).…”
Section: Comparative Proteomic Analyses Of Strains Lacking Yfgm-supporting
confidence: 79%
“…types identified in the ⌬skp and ⌬surA strains (i.e. compromised outer membrane integrity and activation of cell envelope stress responses) are exacerbated when yfgM is deleted (13). It is therefore possible that Skp and SurA compensate for the absence of YfgM and prevent the identification of some potential substrates.…”
Section: Comparative Proteomic Analyses Of Strains Lacking Yfgm-mentioning
confidence: 99%
See 2 more Smart Citations
“…Protein BLAST searches indicated that FTS_1680 and FTS_1681 share 28% identity (query cover 93%; E value ϭ 2eϪ15) with YfgM (which contains TPR motifs) of E. coli K-12 and 26% identity (query cover 94%; E value ϭ 6eϪ48) with YfgL of E. coli K-12. Proteins YfgM and YfgL are linked to temperature tolerance (28), and very recently YfgM has been described as a protein involved in the SecYEG system of E. coli (29). To exclude possible polar effects on downstream genes, we evaluated levels of The inFTS_1680 mutant escapes into the host cell cytosol to a lesser extent than the wild-type FSC200 strain.…”
Section: Fig 3 Fts_1680 Is Important For Virulence In Murine Model Ofmentioning
confidence: 99%